PENGARUH PASIR BATU BREKSI SEBAGAI PENGGANTI AGREGAT HALUSDITINJAU DARI KUAT TEKAN DAN MODULUS ELASTISITAS BETON - Nosepa Cahyo, Yurri; Adi Sambowo, Kusno; Supardi, Supardi (Matriks Teknik Sipil, 2014)
The Study of effect of breksi stone as a substitute for fine aggregate in concrete mix aims to find value of compressive strength and modulus ofelasticity, and determine the feasibility of using concrete and breksi stone as structural concrete. In this study, writer used an experimental methodat laboratory. Writer tests fine aggregates (sand), coarse aggregate, sand stone and breksi stone as components of concrete. After component meet therequirements, they are tested to find compressive strength and modulus of elasticity by using specimen cylinder, measured 15 cm x 30 cm withvariation of breksi stone on level 0%, 20 %, 40 %, 60 %, 80 %, and 100 % toward the weight of the fine aggregate in the concrete mix. Fromthe test, writer find the value of compressive strength and modulus of elasticity tends to decrease after the substitution with breksi stone. Averagevalues of concrete compressive strength on 28 days is 36.768 MPa (0% breksi stone); 30.92 MPa (20% breksi stone); 28.28 MPa (40%breksi stone); 25.27 MPa (60% breksi stone); 22.63 MPa (80% breksi stone); 19.609 MPa (100% breksi stone). Average values of modulusof elasticity value are 28062.67 MPa (0% breksi stone), 21614.00 MPa (20% breksi stone), 19643.67 MPa (40% breksi stone), 18728.00MPa (60% breksi stone), 17814.00 MPa (80% breksi stone), 14709.00 MPa (100% breksi stone). From the test results to 5 levels ofvariation of breksi stone, the variation of 0% to 80% indicates that the compressive strength qualifies as a structural concrete, except at 100%levels have a compressive strength below 20 MPa, which is 19.609 MPa.